2017
DOI: 10.26505/djm.13023540813
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ramadan Fasting on Healthy Adult Males: Immuno-Bio-Chemical Study

Abstract: Background: The mandatory month is Ramadan on Muslim's fasting. Muslims cease from ingestion of food and water starting onset to grass widower to who wants to be fasting in this month that's according to the lunar calendar; so many immunological, physiological and biochemical changes may happen. Objective: To evaluate some vitamins, hormones and immunological markers in the first and the 28th day of fasting. Patients and Methods: Twenty five healthy adult male who were subjected to this study. The age range wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Till date, very few studies have been done specifically looking at TSH variations based on change of timing of administration of levothyroxine during Ramadan [7, 10, 11]. Some studies have suggested that proper administration of levothyroxine during Ramadan is an hour before suhour; however, this suggestion was not followed by most of the patients, as they feel it was difficult to wake up early in the morning [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Till date, very few studies have been done specifically looking at TSH variations based on change of timing of administration of levothyroxine during Ramadan [7, 10, 11]. Some studies have suggested that proper administration of levothyroxine during Ramadan is an hour before suhour; however, this suggestion was not followed by most of the patients, as they feel it was difficult to wake up early in the morning [12].…”
Section: Discussionmentioning
confidence: 99%
“…The thyroid hormone level variables between the levothyroxine dosage in suhour and iftar were measured by performing an independent samples t-test. All P values less than 0.05 were considered to be statistically significant [7].…”
Section: Methodsmentioning
confidence: 99%